Detection of Antibiotic Residues in Food Using Biosensors: A Review - Avaya Prabha, M.M.; Dharini, V.; Aishwarya, B.; Jaswanth Sha Allan, M.; Periyar Selvam, S.; Mahesh Kumar, M. (Asian Journal of Chemistry, 2021)
Over the years, antibiotics and their implementation have been even more erratic and ambitious, considering their reputation and clinical relevance. In modern times, the medicinal use of antibiotics is important for the treatment of a wide variety of microbial infections. The misuse and overuse of antibiotics have contributed dramatically to the elicitation of antibiotic-resistant bacteria (ARB) that has become a global concern. Those immune to the medication live and reproduce as bacteria are repeatedly exposed to low doses of an antibiotic, while the remainder dies off, resulting in a new population of bacteria that avoids the use of antibiotics. Antibiotics residues in food products/byproducts are metabolites present in trace levels in any edible portion of animal product after administration of antibiotics. The antibiotics residues in food which lies in excess than that of acceptable range of maximum residue limit contribute in development of antibiotic resistances among animals/humans. In dairy industries, rapid advancements in technology are being made and food processing technology has started to focus on biosensors to assess the consistency of food products. Biosensors are instruments that contain a biochemical molecule that produces a tactile signal which is transformed into an indication to assess the consistency and protection of food. In recent years, when the devices began to grow constantly with their extensive deployment in the food industries, current traditional methods that have historically been introduced replaced them. The goal of the following review is to provide a thorough overview of biosensors and their forms that differ depending on the substrate involved and highlight the insights that rule the importance of biosensors in antibiotic residue detection.